The Relation Between Emotional Intelligence And Job Satisfaction (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Nowadays, in almost all fields, analysis of relation between Job  Satisfaction and Emotional Intelligence has been one of the most crucial  research subjects to get high productivity. These two are the main  concepts in modern work environment. This paper aims at studying  relationship between Job Satisfaction and Emotional Intelligence. For  this reason, 50 managers of Government Banks were chosen (random  stratified sample) and the data was gathered by running Sibria Shiring  Emotional Intelligence Questionnaire and Bray field & Rothe Job  Satisfaction Questionnaire. After that, to analyze the data, Pearson  correlation analysis was done. Results showed that there is a relation  between Emotional Intelligence and Job Satisfaction. The relation  between job satisfaction and each of the emotional intelligence criteria  (self-awareness, self-control, self motivation, Intimacy and social skills)  were upheld. The analysis gave a positive relation between two  variables. This study will help various researchers and practitioners in  realising the link between these two variables.
Keywords: Emotional Intelligence; Job Satisfaction; productivity